Congelamento ultra-rápido de embriões bovinos com etilenoglicol associado ou não a trealose - Pilla, Luiz Fernando Caceres (2005)
Cryopreservation is currently the universal method for embryo storage, transport, sanitary control and trading. The conventional bovine embryo freezing method still has some drawbacks such as the freezing period and costs of the freezing equipment. In order to decrease costs and time, the effect of thealose on ultra-rapid freezing with ethylene glycol was evaluated. Ninety seven in vivo produced bovine embryos were randomly distributed in two treatments for ultra-rápid deep freezing with 3.M ethylene glycol (T1; n= 46) and 3.M ethylene glycol + 0.3M trehalose (T2; n= 51). In T1, embryos were exposed to a 3.0M ethylene glycol in Emcare® (ICP) holding media and in T2 to a 3.0M ethylene glycol plus 0.3M trehalose in Emcare® holding media. Embryos of both treatments were kept for 2 minutes in the freezing solutions; loaded in 0,25cc straws and there after they were exposed to N2 vapor during 20 seconds to be plunged immediately into liquid nitrogen. After thawing, embryos were transferred to previously synchronized recipients resulting at 28 days in 7 (15.21%) pregnancies in T1 and also 7 (13.72%) in T2. No significant difference was detected between treatments (P>0.05). The trehalose and ethylene glycol solution is suitable for direct transfer of bovine embryos. However, the conception rate obtained in this study do not allow its indication for commercial embryo freezing.